臺灣與馬來西亞教保服務人員對幼兒性不當對待防治的 認知與實踐跨國比較 - 鄭伊倩 Yz-Qian Tay; 張明麗 Ming-Li Chang; 胡家珮 Jia-Pei Hu; 高碩亨 Shuo-Heng Gao (National Changhua University of Education, 2022)
本研究旨在探討臺灣與馬來西亞教保服務人員，對幼兒性不當對待防治認知與實踐的表現及差異。首先訪談 2 位臺灣教保服務人員，根據訪談結果與相關文獻，初擬問卷 24 題，接著請 2 位臺灣、4 位馬來西亞學術與實務工作者進行專家審核以建立效度。隨後對 51位臺灣與 53 位馬來西亞教保服務人員進行預試，以項目分析、雙變數相關分析、信度分析、因素分析進行刪題，以 Cronbach α 進行信度考驗，形成 24 題正式問卷，之後對471 位臺灣與 353 位馬來西亞教保服務人員進行正式施測。研究結果發現：兩國教保服務人員，在幼兒性不當對待防治的認知與實踐存在差異；且臺灣的認知與實踐皆優於馬來西亞。根據研究結果，事後訪談 4 位教保服務人員，補充造成該結果的原因。本研究提出相關建議，供教育行政單位與未來相關研究參考。 This study examined the performances and differences between Taiwanese and Malaysian preschool educators in their cognition and practice of prevention and treatment of child sexual abuse, especially for preschoolers. We initially interviewed two Taiwanese preschool educators. Based on the interview results and related literature, a preliminary 24-item questionnaire was drafted, and then two Taiwanese and four Malaysian academics and practitioners were invited to participate in expert validity. A preliminary test was conducted on 51 Taiwanese and 53 Malaysian preschool educators. Through an item analysis, bivariate correlation analysis, reliability analysis, and factor analysis, some items in the questionnaire were deleted. A formal 24-item questionnaire was developed using Cronbach's alpha tests for further reliability verification. Subsequently, a formal survey was conducted on 471 Taiwanese and 353 Malaysian preschool educators. The research results reveal that preschool educators in both countries showed differences between their cognition and practice in the prevention and treatment regarding child sexual abuse. In addition, Taiwanese preschool educators demonstrated a better performance than their Malaysian counterparts in both cognition and practice. According to the results of the study, four preschool educators were interviewed afterward to add to the reasons of such results. Suggestions for the promotion of preventing children's sexual abuse were offered in terms of subjects, the combination of teaching and researching for university teachers, and future research.